A comparative computational investigation on the proton and hydride transfer mechanisms of monoamine oxidase using model molecules - ERDEM, SAFİYE (ELSEVIER SCI LTD, 2013)
Monoamine oxidase (MAO) enzymes regulate the level of neurotransmitters by catalyzing the oxidation of various amine neurotransmitters, such as serotonin, dopamine and norepinephrine. Therefore, they are the important targets for drugs used in the treatment of depression, Parkinson, Alzeimer and other neurodegenerative disorders. Elucidation of MAO-catalyzed amine oxidation will provide new insights into the design of more effective drugs. Various amine oxidation mechanisms have been proposed for MAO so far, such as single electron transfer mechanism, polar nucleophilic mechanism and hydride mechanism. Since amine oxidation reaction of MAO takes place between cofactor flavin and the amine substrate, we focus on the small model structures mimicking flavin and amine substrates so that three model structures were employed. Reactants, transition states and products of the polar nucleophilic (proton transfer), the water-assisted proton transfer and the hydride transfer mechanisms were fully optimized employing various semi-empirical, ab initio and new generation density functional theory (DFT) methods. Activation energy barriers related to these mechanisms revealed that hydride transfer mechanism is more feasible. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Monoamine oxidase; Enzyme mechanisms; Flavoenzymes; FAD; Water-assisted mechanism; DFT methods; AMINE-OXIDATION; DENSITY FUNCTIONALS; CATALYZED OXIDATION; BOND-CLEAVAGE; PM6 METHOD; MAO-A; INSIGHTS; BENZYLAMINE; RESOLUTION